Nonlinear Compensation Empyoing Matrix Converter with DTC Controller - Khalaf S. Gaied; Ziad H. Salih; Ahmed R. Ajel; Mehdi J. Marie (Institute of Advanced Engineering and Science, 2017)
This paper describes a nonlinear harmful speed and torque controller for fourth order induction motor model. The investigation of optimality and cost function for that base on estimation of Hammerstein-Wiener model with the compensated mathematical model. The matrix converter with direct torque control combination is efficient way to get better performance specifications in the industry.The MC and the DTC advantages are combined together.The reduction of complexity and cost of DC link in the DTC since it has no capacitors in the circuit. However, the controlling torque is a big problem it in DTC because of high ripple torque production which results in vibrations response in the operation of the IM as it has no PID to control the torque directly. The combination of MC with DTC is applied to reduce the fluctuation in the output torque and minimize the steady state error. This paper presents the simulation analysis of induction machine drives using Maltlab/Simulink toolbox R2012a. Design of constant switching frequency MCDTC drive,stability investigation and fault protection as well as controllability and observability with minimum steady state error has been carried out which proved the effectiveness of the proposed technique.